Direct Fed Microbial, Primalac®, Supplementation and Jejunal Glucose and Proline Transport in Broiler Chickens - Chichlowski, M.; Croom, J.; Qui, R.; McBride, B.W.; Koci, M.D. (International Journal of Poultry Science, 2008)
Direct fed microbials (DFM) are a putative alternative to the feeding of subtherapeutic levels of antibiotics in poultry production. Previous studies with a DFM, Primalac®, have suggested that DFM may decrease ileal energy expenditures in broilers. These changes might be related to nutrient transport in the gastrointestinal (GI) tract. The current study examined the effects of supplementing broiler diets with DFM on ileal glucose and proline absorption and their relationships to GI energy expenditures. Twenty-four broiler chickens were fed a standard starter diet (CON) and CON + DFM, (PrimaLac® 0.3% w/w) from hatch to 3 wk of age. On d 21, birds were euthanized, ileal tissue was dissected and glucose and proline uptake were estimated. In adjacent tissue, total O2 (TO2) and oubain (Na/K ATPase-sensitive) O2 consumption were estimated. Primalac® had no effect (P>0.05) on ileal glucose and proline absorption transport rates as well as oubain sensitive and non-oubain sensitive oxygen consumption rates. Total passive transport of proline across the entire ileum was decreased by Primalac®.